Effects of partial clearing on microclimate in a humid tropical forest - Ghuman, B.S.; Lal, R. (1987)
We have measured and compared several microclimatic variables in a cleared area and under a high rain forest in the humid tropic belt of Nigeria. Measurements were made consecutively from July to December for the years 1984 and 1985. Throughfall under forest was about 12 and 32% less than rainfall received in the cleared area in 1984 and 1985, respectively. The relative humidity was higher in the forest than the cleared area during rainy months but the effect was less pronounced during dry months. Solar radiation was 25- to 30-times less, and open pan evaporation 4- to 6-times less under forest than in the cleared site. Wind speed, measured in 1986, was about 18 times less in the forest than the cleared area. On a clear day, the maximum soil temperature at 1 cm depth was 3–10°C lower under forest than in the cleared area. However, the difference in the maximum soil temperatures was less on cloudy days (3°C). Air temperature during the rainy season was lower by 1–5°C under forest than in the cleared area.